Pengaruh Transformasi Digital, Praktik Green Inovation dan Integrasi Rantai Pasokan (SCI) dalam meningkatkan Sustainable Business UMKM di Bekasi - Alifah Nurul Fauziah; Putri Yusnia; Nasyila Alika (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of the digital economy and increasing demands for business sustainability are encouraging MSMEs to adapt to changes in the business environment. However, in practice, MSMEs still face various challenges in maintaining business sustainability, such as limited environmentally friendly innovation and weak supply chain integration. The purpose of this study is to analyze the effects of digital transformation, green innovation, and supply chain integration on business sustainability in MSMEs in Bekasi Regency. This study uses a quantitative approach with an explanatory research method. The unit of analysis in this study is MSME actors, with a sample size of 100 respondents. The data were analyzed using classical assumption tests and multiple linear regression. The results show that, partially, digital transformation does not have a significant effect on business sustainability, while green innovation and supply chain integration have a significant effect. Simultaneously, digital transformation, green innovation, and supply chain integration have a significant effect on business sustainability, indicating that environmentally friendly innovation and supply chain integration play an important role in supporting the sustainability of MSME businesses.